Characterizing and Tuning the Properties of Polydiacetylene Films for Sensing Applications - Finney, Tanner J (Langmuir : the ACS journal of surfaces and colloids, 2021)
Self-assembled, polymerized diacetylene (DA) nanostructures and two-dimensional films have been studied over the past two decades for sensor applications because of their straightforward visual readout. DA monomers, when exposed to UV light, polymerize to produce a visibly blue polymer. Blue phase polydiacetylenes (PDAs) when exposed to an external stimuli, such as temperature or UV light, undergo a chromatic phase transition to a fluorescent, visibly red phase. The tunability of the monomer to blue to red chromatic phase transitions by choice of diacetylene monomer in the presence of metal cations is systematically and comprehensively investigated to determine their effects on the properties of PDA Langmuir films. The polymerization kinetics and domain morphology of the PDA films were characterized using polarized fluorescent microscopy, UV-vis-fluorescent spectroscopy, and Fourier transform infrared spectroscopy (FTIR). Increasing the monomer alkyl tail length was found to strongly increase the UV dose necessary to produce optimally blue films and fully red films. A decrease in the polymer domain size was also correlated with longer-tailed DA molecules. Metal cations have a diverse effect on the film behavior. Alkaline-earth metals such as Mg, Ca, and Ba have a negligible effect on the phase transition kinetics but can be used to tune PDA polymer domain sizes. The Ni and Fe cations increase the UV dose necessary to produce red phase PDA films and significantly decrease the polymer domain sizes. The Zn, Cd, and Cu ions exhibit strong directed interactions with the PDA carboxylic acid headgroups, resulting in quenched fluorescence and a unique film morphology. FTIR analysis provides insight into the metal-PDA binding mechanisms and demonstrates that the coordination between the PDA film headgroups and the metal cations can be correlated with changes in the film morphology and kinetics. The findings from these studies will have broad utility for tuning PDA-based sensors for different applications and sensitivity ranges